International Trade, Environmental Degradation, and Human Rights Challenges in Indonesia - Rahmani, Parwana (Unisia, 2025)
This article examines the impacts of international trade on human rights and environmental protection in Indonesia, with the aim of explaining how increased integration into the global trading system has generated significant ecological degradation and, in turn, undermined the fulfillment of fundamental human rights. Using a qualitative descriptive and analytical methodology, the study relies on literature review of academic works, international legal instruments, national legislation, policy documents, and selected empirical cases related to trade, foreign direct investment, and natural resource exploitation in Indonesia. The analysis shows that international trade expansion has contributed to deforestation, water and air pollution, land degradation, and rising greenhouse gas emissions, particularly in sectors such as forestry, agriculture, mining, and manufacturing. These environmental impacts are closely linked to violations of human rights, including the rights to a healthy environment, clean water, adequate food, health, and the protection of indigenous communities. Drawing on dependency theory and the environmental human rights framework, the article argues that unequal global trade relations and weak domestic governance have intensified environmental burdens in developing countries like Indonesia. Although Indonesia has adopted various national laws and is party to international human rights and environmental agreements, enforcement remains inadequate due to weak regulatory oversight, limited accountability of corporations, and insufficient protection for affected communities. The study concludes that international trade, when not accompanied by strong environmental governance and human rights safeguards, poses serious risks to sustainable development. It highlights the need for stricter regulation, effective law enforcement, and the integration of human rights principles into trade and environmental policies to ensure that economic growth does not come at the expense of environmental sustainability and human dignity.